Rural schools in the municipality of Anchieta- SC: continued training of education professionals - Simon, Cleonice; Bavaresco, Paulo Ricardo (Seven Editora, 2023)
The article aims to present the type of education offered to peasants, with emphasis on the conditions of rural teachers who seek to offer an education designed to value the subject, as agents capable of contributing to the transformation of society. Therefore, from the problematization of the dichotomy between urban and rural schools, the main movements already developed in favor of the rights of the peasant population will be mentioned, as is the case of the creation of the LDBEN (Law of Guidelines and Bases of National Education) and the MST (Landless Movement). This is an applied research, with a quantitative and qualitative approach and an exploratory purpose, designed based on two electronic questionnaires that, due to the Covid-19 pandemic and social isolation, were applied through the email of students and teachers from two schools in the interior of the municipality of Anchieta/SC. Data collection took place between February and May 2020 and the analysis was performed using the Bardin methodology. Ten professors and forty-nine students participated in the research. The results showed that, despite the existence of difficulties related to the lack of teacher training to meet the real needs of students in rural areas, there is an awareness on the part of the participants regarding the need for public policies that encourage continuing education courses as a means of to guarantee a better professional qualification, as well as to develop a teaching methodology capable of encouraging the population to remain in the countryside. DOI: https://doi.org/10.56238/devopinterscie-050